Synthesis of benzofulvenes through chemoselective Sonogashira and Barluenga couplings of ortho ethynyl-N-tosylhydrazones and cycloisomerization1. Issue 91 (9th October 2015) - Aziz, Jessy; Brion, Jean-Daniel; Alami, Mouad; Hamze, Abdallah
<x xml:space="preserve">Abstract</x> Chemoselective synthesis of ortho ethynylhydrazones 7 derived from 2-iodoacetophenone via a Sonogashira coupling is reported for the first time.